Participant experiences using novel home-based blood collection device for viral load testing in the HIV cure trials with analytical treatment interruptions. Issue 1 (2nd August 2022) - Dubé, Karine; Agarwal, Harsh; Carter, William B.; Dee, Lynda; Taylor, Jeff; Roebuck, Christopher; Peterson, Beth; Patel, Hursch; Ndukwe, Samuel; Lynn, Kenneth M.; Lalley-Chareczko, Linden; Hiserodt, Emily; et al.
Abstract : Background : HIV cure-directed clinical trials using analytical treatment interruptions (ATIs) require participants to adhere to frequent monitoring visits for viral load tests. Novel viral load monitoring strategies are needed to decrease participant burden during ATIs. Objective : To examine acceptability of a novel home-based blood collection device for viral load testing in the context of two ongoing ATI trials in Philadelphia, PA, United States. Methods : From January 2021 to February 2022, participants completed three in-depth interviews via teleconference during their participation in an ATI: (1) within two weeks of enrollment in the device study, (2) approximately four weeks after beginning to use the device, and (3) within two weeks of the end of the ATI when ART was re-initiated. We used conventional content analysis to analyze the data. Results : We recruited 17 participants: 15 were cisgender males, 1 cisgender female, and 1 transgender woman. We observed an overall 87% success rate in drawing blood with the device from home collection and found overall high acceptance of the device. A mean of 91.5 devices per participant were used for home-based blood collection. Most PWH viewed the device as relatively convenient, painless, easy to use, and a simple solution to frequent blood draws. The main challenge encountered was the inability to completely fill up devices with blood in some cases. Most participants reported positive experiences with mailing blood samples and could see themselves using the device on a regular basis outside of ATIs. Conclusions : Our study showed participant valued the novel home-based peripheral blood collection for viral load testing in the context of ATI trials. More research will be necessary to optimize implementation of the device and to assess whether blood collected can reliably measure viral loads in the context of ATI trials.